Application of automated immunohistochemistry in anatomical research: A brief review of the method - Michał Golberg; Grzegorz Wysiadecki; Józef Kobos; Piotr Brzeziński; Michał Polguj; Edward Clarke; Karolina Barszcz; Krzysztof Balawender; Maciej Radek; Andrzej Żytkowski (Elsevier, 2022)
Background: To meet modern requirements, the application of advanced histological techniques in anatomical research must meet methodological standards. Meeting these standards is not easy for many reasons. Difficulties arise both from problems with obtaining high-quality material for research and the fact that the material for anatomical research requires a special approach so that immunohistochemical research brings new insight to the existing anatomical knowledge. For instance, specimens must be appropriately selected, fixed, processed, embedded in the correct plane in a paraffin block, properly cut, and the sections obtained must be on the suitable types of slides. The tissue quality and time from the donor death to the collection and fixation of the material is crucial, and the storage time of the material in the fixative is also essential. Aim: Since anatomical research is often carried out on troublesome and challenging material, there is a need for a simple compendium of knowledge on the fundamental issues of applying automated immunohistochemistry. Conclusions: All basic immunohistochemistry steps can be conducted automatically with an autostainer. Timings, reagents volumes, number of wash buffer rinses are fixed in the core protocol provided by the autostainer's producer but can be modified depending on individual research requirements.